2004
DOI: 10.1073/pnas.0405031101
|View full text |Cite
|
Sign up to set email alerts
|

A gain-of-function mutation of Fgfr2c demonstrates the roles of this receptor variant in osteogenesis

Abstract: The b and c variants of fibroblast growth factor receptor 2 (FGFR2) differ in sequence, binding specificity, and localization. Fgfr2b, expressed in epithelia, is required for limb outgrowth and branching morphogenesis, whereas the mesenchymal Fgfr2c variant is required by the osteocyte lineage for normal skeletogenesis. Gain-of-function mutations in human FGFR2c are associated with craniosynostosis syndromes. To confirm and extend this evidence, we introduced a Cys342Tyr replacement into Fgfr2c to create a gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
220
1
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(240 citation statements)
references
References 30 publications
16
220
1
3
Order By: Relevance
“…For instance, abnormal cranial bases in achondroplasia and Apert, Crouzon, and Muenke syndromes are caused by mutations in FGFR, indicating that FGF signaling is not only important to the formation of the cranial vault, but also for the cranial base (Horowitz, 1981;Cohen et al, 1985;Kreiborg et al, 1993Kreiborg et al, , 1999Wilkie and Morriss-Kay, 2001;Reinhart et al, 2003). Similar defects have been observed in FGFR transgenic mouse strains Eswarakumar et al, 2002Eswarakumar et al, , 2004. Mutations in RUNX2 and TWIST give rise to cleidocranial dysplasia and Saethre-Chotzen syndromes, respectively, which are characterized by defects in the cranial base (Evans and Christiansen, 1976;Kreiborg et al, 1981;Howard et al, 1997;Lee et al, 1997).…”
supporting
confidence: 60%
“…For instance, abnormal cranial bases in achondroplasia and Apert, Crouzon, and Muenke syndromes are caused by mutations in FGFR, indicating that FGF signaling is not only important to the formation of the cranial vault, but also for the cranial base (Horowitz, 1981;Cohen et al, 1985;Kreiborg et al, 1993Kreiborg et al, , 1999Wilkie and Morriss-Kay, 2001;Reinhart et al, 2003). Similar defects have been observed in FGFR transgenic mouse strains Eswarakumar et al, 2002Eswarakumar et al, , 2004. Mutations in RUNX2 and TWIST give rise to cleidocranial dysplasia and Saethre-Chotzen syndromes, respectively, which are characterized by defects in the cranial base (Evans and Christiansen, 1976;Kreiborg et al, 1981;Howard et al, 1997;Lee et al, 1997).…”
supporting
confidence: 60%
“…Furthermore, we also showed that FGF-2 controls NAMP function in culture through FGFR2c. Interestingly, gain-of-function mutations of FGFR2c, which is expressed during osteogenesis [47], caused impaired differentiation of BM osteoprogenitors and osteoblasts [48], leading to bone malformations characteristic of the Crouzon and Pfeiffer syndromes in patients [49]. Conversely, in FGFR2c À/ À mice, the balance between proliferation and differentiation of skeletal progenitors was shown to be shifted toward differentiation, leading to premature loss of osteoprogenitor selfrenewal and early termination of bone formation [50].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in both FGFR1 and -2 have been implicated in craniofacial syndromes, but are more commonly found in craniosynostosis, premature fusion of sutures due to disrupted intramembranous bone growth (reviewed in Chen and Deng, 2005). Although an in vivo role for Stats downstream of FGFR2 has not yet been shown, mouse models of craniosynostosis containing altered FGFR2, display several phenotypes that overlap with those observed in FKO, Wnt1-Cre; Floxdel/KI, or Tcfap2a ϩ/Ϫ mice including shortened snouts, dental malocclusion, widespaced eyes, and cleft palate (Zhang et al, 1996;Nottoli et al, 1998;De Moerlooze et al, 2000;Hajihosseini et al, 2001;Eswarakumar et al, 2002Eswarakumar et al, , 2004Chen et al, 2003;Brewer et al, 2004;Nelson and Williams, 2004;Wang et al, 2005). Thus, the presence of a STAT site in the FNP/LBM-specific enhancer likely places AP-2␣ downstream of FGFR signaling in the FNP, which is consistent with other studies showing FGF-dependent changes of Tcfap2a in the craniofacial region (Shen et al, 1997;Cordero et al, 2004).…”
Section: Stat Proteins Act Upstream Of Tcfap2amentioning
confidence: 99%